Intervention for critical aortic stenosis in Hutchinson-Gilford progeria syndrome - Gordon, Leslie B.; Basso, Sammy; Maestranzi, Justine; Aikawa, Elena; Clift, Cassandra L.; Cammardella, Antonio Giovanni; Danesi, Tommaso Hinna; del Nido, Pedro J.; Edelman, Elazer R.; Hamdy, Abeer; Hegde, Sheila M.; Kleinman, Monica E.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Hutchinson-Gilford Progeria Syndrome (HGPS) is an ultra-rare genetic premature aging disease that is historically fatal in teenage years, secondary to severe accelerated atherosclerosis. The only approved treatment is the farnesyltransferase inhibitor lonafarnib, which improves vascular structure and function, extending average untreated lifespan of 14.5 years by 4.3 years (30%). With this longer lifespan, calcific aortic stenosis (AS) was identified as an emerging critical risk factor for cardiac death in older patients. Intervention to relieve critical AS has the potential for immediate improvement in healthspan and lifespan. However, HGPS patient-device size mismatch, pervasive peripheral arterial disease, skin and bone abnormalities, and lifelong failure to thrive present unique challenges to intervention. An international group of experts in HGPS, pediatric and adult cardiology, cardiac surgery, and pediatric critical care convened to identify strategies for successful treatment. Candidate procedures were evaluated by in-depth examination of 4 cases that typify HGPS clinicale pathology. Modified transcatheter aortic valve replacement (TAVR) and left ventricular Apico-Aortic Conduit (AAC) placement were deemed high risk but viable options. Two cases received TAVR and 2 received AAC post-summit. Three were successful and 1 patient died perioperatively due to cardiovascular disease severity, highlighting the importance of intervention timing and comparative risk stratification. These breakthrough interventions for treating critical aortic stenosis in HGPS patients could rewrite the current clinical perspective on disease course by greatly improving late-stage quality of life and increasing lifespan. Expanding worldwide medical and surgical competency for this ultra-rare disease through expert information-sharing could have high impact on treatment success.